Genetic diversity, yield, and fruit quality of persimmon in the tropics - Peche, Pedro Maranha; Pio, Rafael; Badenes, María Luisa; Naval, Mar; Gil-Muñoz, Francisco; Bianchini, Flávio Gabriel; Locatelli, Guilherme (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to determine the genetic diversity, yield, and fruit quality of persimmon genotypes grown in the tropics, in order to select promising genetic materials. DNA extraction was performed on young leaves of 19 persimmon genotypes. For pomological characterization, 15 genotypes were selected. From each genotype, 50 fruit at the physiological maturity stage were harvested in the morning, in order to determine the following parameters: physicochemical characteristics; and the productive variables number of fruit per plant, average fruit fresh mass, average yield, and estimated average yield in two seasons. Twenty SSR markers were tested, out of which 12 were selected to evaluate genetic similarity, which allowed of the identification of distinct groups. The mean genetic diversity value found was 0.41, which is an indicative of low diversity among the analyzed persimmon genotypes. The ’Guiombo’, ’Iapar 125’, ’Kakimel’, ’Mikado RJ’, ’Rama Forte Tardio’, and ’Taubaté’ genotypes show a high yield. The genotypes classified as pollination-constant astringent (’Pomelo’, ’Regina’, ’Rubi’, and ’Taubaté’) and those classified as pollination-variant astringent (’Rama Forte’, ’Guiombo’, and ’Cereja’) are potential materials for selection and genetic breeding programs due to their excellent fruit physicochemical characteristics. The investigation through molecular markers is an efficient approach to study the genetic diversity of persimmon genotypes grown in the tropics.